Genetic Approaches to Increase Arabinoxylan and β-Glucan Content in Wheat - Anneke Prins; Ondrej Kosik (Plants, 2023)
Wheat is one of the three staple crops feeding the world. The demand for wheat is ever increasing as a relatively good source of protein, energy, nutrients, and dietary fiber (DF) when consumed as wholemeal. Arabinoxylan and β-glucan are the major hemicelluloses in the cell walls and dietary fiber in wheat grains. The amount and structure of DF varies between grain tissues. Reducing post-prandial glycemic response as well as intestinal transit time and contribution to increased fecal bulk are only a few benefits of DF consumption. Dietary fiber is fermented in the colon and stimulates growth of beneficial bacteria producing SCFA, considered responsible for a wide range of health benefits, including reducing the risk of heart disease and colon cancer. The recommended daily intake of 25–30 g is met by only few individuals. Cereals cover nearly 40% of fiber in the Western diet. Therefore, wheat is a good target for improving dietary fiber content, as it would increase the fiber intake and simultaneously impact the health of many people. This review reflects the current status of the research on genetics of the two major dietary fiber components, as well as breeding approaches used to improve their quantity and quality in wheat grain.